2017
DOI: 10.1371/journal.pgen.1006748
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of INF2-mediated mitochondrial fission in SPOP-mutated prostate cancer

Abstract: Next-generation sequencing of the exome and genome of prostate cancers has identified numerous genetic alternations. SPOP (Speckle-type POZ Protein) was one of the most frequently mutated genes in primary prostate cancer, suggesting SPOP is a potential driver of prostate cancer development and progression. However, how SPOP mutations contribute to prostate cancer pathogenesis remains poorly understood. SPOP acts as an adaptor protein of the CUL3-RBX1 E3 ubiquitin ligase complex that generally recruits substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…TLR4 activation causes the translocation of SPOP to the cytoplasm Recently, it was demonstrated that SPOP is located in both the cytoplasm and nucleus, although it was previously considered a nuclear protein. 34 Because SPOP is associated with MyD88 following TLR4 activation, we sought to determine whether SPOP is translocated to the cytoplasm after TLR4 activation. We isolated nuclear and cytoplasmic fractions and found that SPOP was mainly located in the nucleus, and only a small amount of SPOP was detected in the cytoplasm (Fig.…”
Section: Identification Of Spop As a Myd88-associated Proteinmentioning
confidence: 99%
“…TLR4 activation causes the translocation of SPOP to the cytoplasm Recently, it was demonstrated that SPOP is located in both the cytoplasm and nucleus, although it was previously considered a nuclear protein. 34 Because SPOP is associated with MyD88 following TLR4 activation, we sought to determine whether SPOP is translocated to the cytoplasm after TLR4 activation. We isolated nuclear and cytoplasmic fractions and found that SPOP was mainly located in the nucleus, and only a small amount of SPOP was detected in the cytoplasm (Fig.…”
Section: Identification Of Spop As a Myd88-associated Proteinmentioning
confidence: 99%
“…Similarly, the energy-sensing AMPK increased recruitment of DRP1 to mitochondria via phosphorylation of the MFF and ( 61 ). Speckle-type POZ protein loss-of-function mutations commonly found in primary prostate cancer were associated with increased DRP1 activation, mitochondrial fission, and prostate cancer cell invasion ( 62 ). Recently, loss of expression of the sirtuin SIRT4 was shown to lead to increased mitochondrial fragmentation ( 63 ).…”
Section: Mitochondrial Dynamics In Cancermentioning
confidence: 99%
“…Specifically, SPOP poly-ubiquitinates INF2, which leads not to degradation, but to translocation of INF2 from the ER to the cytosol [Jin et al, 2017]. Consequently, SPOP overexpression or targeting to the cytosol (by elimination of its nuclear localization signal) leads to mitochondrial lengthening.…”
Section: Inf2-dependent Mitochondrial Fissionmentioning
confidence: 99%